PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) UNTUK MENCAPAI HASIL BELAJAR FISIKA MATERI KALOR - Untajana, Adha Marchellino; Untajana, Sally (Atom : Jurnal Riset Mahasiswa, 2024)
This study aims to describe the learning outcomes of science physics students The density material taught using the Think Pair Share (TPS) Type cooperative learning model in grade VII students of SMP Negeri 8 Ambon. The type of research used in this study is a type of descriptive research that aims to describe existing phenomena, which take place now or in the past, and seeks to systematically describe facts and characteristics about the learning outcomes of Science Physics Students. From the research conducted, it showed that in obtaining the initial test results, none of the students completed learning on the Wave material with an average achievement score of 28.09. In the cognitive aspect, as many as 100% of students succeeded in mastering learning indicators, in the affective aspect, as many as 100% of students succeeded in mastering learning indicators, and in the psychomotor aspect, as many as 100% of students succeeded in mastering learning indicators. With an average achievement score on the cognitive aspect is 79.87, on the affective aspect is 73.33 and on the psychomotor aspect is 75.67. Based on the results of the research conducted, it can be concluded that the use of the Think Pair Share (TPS) Type cooperative learning model can help students achieve Physics Science learning outcomes in cognitive, affective, psychomotor, formative tests and final grades with sufficient qualifications. Thus, the use of the Think Pair Share (TPS) type cooperative learning model can activate students in the teaching and learning process.